Artificial Intelligence Driven Electric Vehicle Traction System for Sustainable Transportation - Ahmed, Shoaib (2025)
A Master of Science thesis in Electrical Engineering by Shoaib Ahmed entitled, “Optimizing the Performance of a Microwave Tomography System for Biomedical Applications”, submitted in April 2025. Thesis advisor is Dr. Habib ur Rehman and thesis co-advisors are Dr. Usman Tariq and Dr. Ammar Hasan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).